Impact of ixekizumab on facial psoriasis and related quality of life measures in moderate‐to‐severe psoriasis patients: 12‐week results from two phase III trials. (6th October 2017) - Paul, C.; Guenther, L.; Torii, H.; Sofen, H.; Burge, R.; Lin, C.Y.; Potts Bleakman, A.; Mallbris, L.; Poulin, Y.
Abstract: Background: Facial psoriasis was reported in 17–68% of patients with psoriasis and shown to have a negative impact on patients' personal and health‐related quality of life (HRQoL). Objectives: To explore the association of facial psoriasis with patients' HRQoL and to assess the relationship between ixekizumab (IXE) and improvement in facial psoriasis and changes in HRQoL. Methods: This work reports the combined results of two phase III multicentre, randomized, double‐blind, placebo‐controlled, active‐comparator trials in patients with moderate‐to‐severe psoriasis. Patients received placebo, etanercept (ETN; 50 mg twice weekly) or IXE [80 mg every 4 weeks (Q4W) or every 2 weeks (Q2W)] for up to 12 weeks following an initial 160‐mg dose. HRQoL parameters were analysed based on facial psoriasis status at baseline using analysis of covariance models. Improvement was assessed as percentage of patients with no facial psoriasis. Results: The combined database included 1133 patients with facial psoriasis and 1437 without. Patients treated with IXE whose facial psoriasis cleared had improved Dermatology Life Quality Index 0.1 responses ( P < 0.01) compared with patients with facial psoriasis at Week 12. At Week 12, clearance of facial psoriasis compared with the presence of facial psoriasis was independently associated with significantly better improvement in Psoriasis Skin Appearance Bothersomeness scores in the IXE Q2W treatment group ( P < 0.01). At Week 12, facial clearance and overall Psoriasis Area Severity Index (PASI) improvement were observed in significant numbers of patients treated with IXE compared with ETN and placebo. Facial psoriasis clearance at Week 12 in patients treated with IXE or ETN was positively associated with PASI75 and PASI90 achievement. Conclusion: Facial psoriasis had a larger negative impact on HRQoL than no facial psoriasis. Facial psoriasis clearance was associated with improved HRQoL. Significantly more IXE‐treated patients had rapid facial clearance vs. ETN and PBO, which led to better clinical outcomes.